Multiphasic modelling of bone-cement injection into vertebral cancellous bone - Bleiler, Christian; Wagner, Arndt; Stadelmann, Vincent; Windolf, Markus; Köstler, Harald; Bogner, Andreas; Gueorguiev-Rüegg, Boyko; Ehlers, Wolfgang; Röhrle, Oliver (International Journal For Numerical Methods in Biomedical Engineering, 2015)
Percutaneous vertebroplasty represents a current procedure to effectively reinforce osteoporotic bone via the injection of bone cement. This contribution considers a continuum-mechanically based modelling approach and simulation techniques to predict the cement distributions within a vertebra during injection. To do so, experimental investigations, imaging data and image processing techniques are combined and exploited to extract necessary data from high-resolution μCT image data. The multiphasic model is based on the Theory of Porous Media, providing the theoretical basis to describe within one set of coupled equations the interaction of an elastically deformable solid skeleton, of liquid bone cement and the displacement of liquid bone marrow. The simulation results are validated against an experiment, in which bone cement was injected into a human vertebra under realistic conditions. The major advantage of this comprehensive modelling approach is the fact that one can not only predict the complex cement flow within an entire vertebra but is also capable of taking into account solid deformations in a fully coupled manner. The presented work is the first step towards the ultimate and future goal of extending this framework to a clinical tool allowing for pre-operative cement distribution predictions by means of numerical simulations.
UnivIS-Import:2016-06-01:Pub.2015.tech.IMMD.lsinfs.multip
Keywords: Anisotropic permeability; Bone-cement injection; Image processing; Multiphasic model; Theory of porous media (TPM); Vertebroplasty